THE RELATIONSHIP BETWEEN ENTREPRENEURIAL MOTIVATION AND ADVERSITY INTELLIGENCE FOR MASS COMMUNICATION STUDENTS - Sudarmaji Sudarmaji; Suci Purwandari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Total workforce in February 2021 was 139.81 million people, an increase of 1.59 million people compared to August 2020. The working population was 131.06 million people, an increase of 2.61 million people from August 2020. Employment fields that experienced a percentage increase The largest sector is the Provision of Accommodation and Food and Drink (0.34 percentage points). The percentage of underemployed decreased by 1.48 percentage points, while the percentage of part-time workers increased by 1.13 percentage points compared to August 2020. There are 19.10 million people (9.30 percent of the working age population) affected by Covid-19. Consists of unemployment due to Covid-19 (1.62 million people), Non-Work Force due to Covid-19 (0.65 million people), temporarily not working due to Covid-19 (1.11 million people), and residents workers who experienced a reduction in working hours due to Covid-19 (15.72 million people). Based on these data, this study aims to determine the relationship between Entrepreneurial Motivation and Adversity Intelligence for Vocational Students in the final semester of the Mass Communication study program in their readiness to face the challenges of the world of work. Collecting data through the distribution of questionnaires. The results of the analysis show that the contribution of Entrepreneurial Motivation with Adversity Intelligence is 11% while the other 89% is explained by other factors.